Interactions between inducible isoforms of nitric oxide synthase and cyclo-oxygenase in vivo: investigations using the selective inhibitors, 1400W and celecoxib - Hamilton, Lorna C (1998)
1. Exposure of tissues to endotoxin (LPS) and/or cytokines leads to the induction of both inducible nitric oxide synthase (iNOS) and cyclo-oxygenase-2 (COX-2). It has previously been reported that there is `cross-talk' between these two systems. However, such previous studies have been limited by the availability of highly selective inhibitors. Here we have investigated the interactions between iNOS and COX-2 in vivo using 1400W, an iNOS-selective inhibitor, and celecoxib, a COX-2-selective inhibitor. 2. Infusion of LPS to rats for 6 h caused a time-dependent increase in the plasma concentrations of 6 keto-prostaglandin F(1α) (6 keto-PGF(1α)) and nitrite/nitrate (NO(2)/NO(3)), consistent with the induction of iNOS and COX-2. Bolus injection of arachidonic acid (AA) at t=6 h resulted in a further increase of circulating levels of 6 keto-PGF(1α) in LPS-treated animals. 3. Treatment of rats with 1400W or the non-selective NOS inhibitor N(G)-monomethyl-L-arginine (L-NMMA) inhibited the increase in plasma NO(2)/NO(3) but were both without effect on the plasma concentration of 6 keto-PGF(1α) before or after AA. 4. Treatment with the non-steroidal anti-inflammatory drugs (NSAIDs), A771726 or diclofenac, or with celecoxib significantly reduced the increase in circulating 6 keto-PGF(1α) caused by LPS, and the large increase in 6 keto-PGF(1α) following injection of AA. None of the COX inhibitors affected the increase in plasma NO(2)/NO(3). Dexamethasone, however, significantly inhibited both the increase in 6 keto-PGF(1α) and the increase in NO(2)/NO(3). 5. In conclusion, the use of selective inhibitors does not support the concept of cross talk in vivo between iNOS and COX-2.